1976
DOI: 10.3171/jns.1976.44.3.0313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with extra-intracranial arterial anastomosis in 65 cases

Abstract: Clinical results of an extra-intracranial arterial bypass (EIAB) procedure for cerebral ischemia are assessed in 65 patients. The 5-year-study suggests that the EIAB procedure has a protective effect against further clinically significant cerebrovascular accidents in properly selected patients. Correlation with angiography and regional cerebral blood flow (rCBF) studies are discussed. It is felt that rCBF measurements offer the best diagnostic test to determine which patients are suitable for surgery by reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…After focal ischemic attacks symptoms may recover completely or partially either shortly after the occurrence of the deficits or more rarely with long intervals after the onset, and such improvements may occur spontaneously, 35 or after surgical revascularization, [36][37][38] perfused at a value insufficient for functional activity but adequate for structural integrity. Slight flow increases restore function in viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…After focal ischemic attacks symptoms may recover completely or partially either shortly after the occurrence of the deficits or more rarely with long intervals after the onset, and such improvements may occur spontaneously, 35 or after surgical revascularization, [36][37][38] perfused at a value insufficient for functional activity but adequate for structural integrity. Slight flow increases restore function in viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s and early 1980s, multiple small retrospective case series documented the safety record and apparent efficacy of this procedure. 2,8,18,43,46,50 While the majority of these studies included patients with heterogeneous disease processes (for example, intracranial anterior circulation stenosis, intracranial posterior circulation stenosis, extracranial ICA stenoocclusion, moyamoya disease, and ICA dissection), the minority focused on patients with symptomatic extracranial ICA occlusion.…”
Section: Historical Background and Existing Evidencementioning
confidence: 99%
“…4 Bypass procedures utilizing the STA as the graft of choice have played an important role in certain cases of occlusive disease, complex aneurysms, and tumors. 1,5,6,8,10,12,13,16,19,32,33 Despite the 1985 randomized trial 3 that indicated no increased benefit of the STA-MCA bypass over medical therapy for atherosclerotic lesions of the ICA, this therapeutic option remains available in the management of a subset of patients with occlusive cerebrovascular disease.…”
Section: Superficial Temporal Arterymentioning
confidence: 99%